Alveolar Soft Part Sarcoma Metastatic to Small Bowel Mucosa Causing Polyposis and Intussuseption. (2001) - Sabel, Michael S.; Gibbs, John F.; Litwin, Allan; Mcgrath, Brian; Kraybill, William B.; Brooks, John J.
Abstract : A report of alveolar soft part sarcoma metastatic to the small bowel is presented. Hematogenous metastases to the small bowel from primary tumors outside the abdominal cavity are uncommon, and most remain asymptomatic and are not discovered until autopsy. However, small bowel metastases can lead to intestinal obstruction, intussuseption or even perforation. While metastases to the small bowel have been described for other tumor types, including melanoma and lung cancer, this is extremely uncommon for sarcoma, especially alveolar soft part sarcoma. We describe a 42-year-old male with a long history of alveolar soft part sarcoma, metastatic to the lung and brain, who developed an intussuseption from metastases to the small bowel.